An examination of the literature on self-regulated learning in EFL education: a bibliometric analysis - Linling Zhong (Cogent Education)
This study employs a bibliometric analysis to examine the research of self-regulated learning (SRL) in English as a Foreign Language (EFL) education. A total of 649 studies were selected from the Web of Science (WOS) and Scopus databases for the analysis. Utilizing the VOSViewer program and Microsoft Excel to reveal the growth trajectory, most-cited countries, international collaborations, most-cited journals and articles, and most-used keywords in the studies. The results demonstrate a significant upward trend from 2002 to 2024, with notable acceleration in recent years. The studies have been mostly cited and published in China, Iran, Japan, New Zealand, and the United States. China has also emerged as a central country for international collaborations. System and TESOL Quarterly are the most cited journals, and the study further identifies the most cited articles. The most-used keywords in the studies revealed a central emphasis on SRL in EFL writing contexts, with strong connections to motivation, self-efficacy, and metacognition. The study contributes to the field by providing a comprehensive overview of current research trends on SRL in EFL education. The findings have implications for researchers, policymakers, and practitioners in EFL education, offering insights into the evolving landscape of SRL research and its potential applications in language learning contexts.